Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics - National Academy of Engineering (The National Academies Press, 2012)
On August 8-12, 2010 the National Academy of Engineering (NAE), with funding from the National Science Foundation (NSF), convened the Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics (STEM), following the release of several reports highlighting the educational challenges facing minority males. The NSF recognized the need to gather input from research communities that focus on minority males about how to frame investigations of gender-based factors that impact learning and choice in STEM education (both at the precollege and higher education levels) and the workforce for minority males. There was particular interest in framing a research agenda to study how interactions between minority males and societal and educational systems (both formal and informal) encourage or discourage the young men's interest and persistence in STEM. In addition, NSF hoped to gain community input to inform the parameters of a future NSF research program that could effectively address minority male participation in STEM. The Colloquy was held at the Mt. Washington Conference Center in Baltimore, Maryland, with approximately 40 participants, most of them researchers in education, psychology, sociology, mathematics, and physics. Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics presents a summary of the Colloquy's breakout and plenary discussions, which addressed (a) research questions articulated in the breakout groups together with theories and methodologies to begin to address these questions; and (b) considerations for a potential research solicitation for the NSF, with major areas of inquiry concerning access, participation, and success for minority males in STEM. This report reflects the views of the individuals who participated in the plenary and breakout groups. It has been reviewed in draft form by persons chosen for their diverse perspectives and expertise in accordance with procedures approved by the National Academies' Report Review Committee. The purpose of this independent review is to provide candid and critical comments that will assist the institution in making its published report as sound as possible and to ensure that the report meets institutional standards for quality and objectivity.

Engineering Societies' Activities in Promoting Diversity and Inclusion: Proceedings of a Workshop–in Brief - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
As part of a series of workshops on the role of engineering societies in engineering education in the United States, the National Academy of Engineering held a workshop titled 201cEngineering Societies2019 Activities in Promoting Diversity and Inclusion201d on June 4, 2018. The goals were to explore how engineering societies can promote diversity and inclusion in engineering, provide an opportunity for societies to share promising practices, and investigate possible collaborative actions. This publication summarizes the presentations and discussions from the workshop.

From Science to Business: Preparing Female Scientists and Engineers for Successful Transitions into Entrepreneurship: Summary of a Workshop - National Research Council (The National Academies Press, 2012)
Scientists, engineers, and medical professionals play a vital role in building the 21st- century science and technology enterprises that will create solutions and jobs critical to solving the large, complex, and interdisciplinary problems faced by society: problems in energy, sustainability, the environment, water, food, disease, and healthcare. As a growing percentage of the scientific and technological workforce, women need to participate fully not just in finding solutions to technical problems, but also in building the organizations responsible for the job creation that will bring these solutions to market and to bear on pressing issues. To accomplish this, it is important that more women in science and engineering become entrepreneurs in order to start new companies; create business units inside established organizations, mature companies, and the government; and\/or function as social entrepreneurs focused on societal issues. Entrepreneurship represents a vital source of change in all facets of society, empowering individuals to seek opportunity where others see insurmountable problems. From Science to Business: Preparing Female Scientists and Engineers for Successful Transitions into Entrepreneurship is the summary of an August 2009 workshop that assesses the current status of women undertaking entrepreneurial activity in technical fields, to better understand the nature of the barriers they encounter, and to identify what it takes for women scientists and engineers to succeed as entrepreneurs. This report focuses on women's career transitions from academic science and engineering to entrepreneurship, with a goal of identifying knowledge gaps in women's skills as well as experiences crucial to future success in business and critical for achieving leadership positions in entrepreneurial organizations. From Science to Business makes the case that in addition to educating women scientists and engineers in rigorous problem solving, it is equally important to provide exposure and training to impart the skills that will enable more women to move from the role of expert to that of leader in dynamic new business enterprises. This book will be of interest to professionals in both academia and industry, graduate and post-graduate students, and organizations that advocate for a stronger economy.

Blueprint for the Future: Framing the Issues of Women in Science in a Global Context: Summary of a Workshop - National Research Council
The scientific work of women is often viewed through a national or regional lens, but given the growing worldwide connectivity of most, if not all, scientific disciplines, there needs to be recognition of how different social, political, and economic mechanisms impact women's participation in the global scientific enterprise. Although these complex sociocultural factors often operate in different ways in various countries and regions, studies within and across nations consistently show inverse correlations between levels in the scientific and technical career hierarchy and the number of women in science: the higher the positions, the fewer the number of women. Understanding these complex patterns requires interdisciplinary and international approaches. In April 2011, a committee overseen by the National Academies' standing Committee on Women in Science, Engineering, and Medicine (CWSEM) convened a workshop entitled, \

Long-Term Impacts of COVID-19 on the Future Academic Careers of Women in STEM: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
On March 23-24, 2022, the National Academies of Sciences, Engineering, and Medicine held a virtual workshop to explore the long-term impact of COVID-19 on the future careers of women in STEM. Workshop participants represented multiple sectors (i.e., higher education, government, and non-profit) as well as various career paths and stages (e.g., assistant, associate, and full professors; graduate students; program officers; directors; and policy advisors). The two-day workshop convened experts and leaders to outline a national research agenda that ensures academic institutions and federal agencies are able to monitor and mitigate the long-term negative impacts of the pandemic on the career trajectories, job stability, and leadership roles of women - especially women of color 2014 in STEM. This publication highlights the presentation and discussion of the workshop.

Seeking Solutions: Maximizing American Talent by Advancing Women of Color in Academia: Summary of a Conference - National Research Council (The National Academies Press, 2013)
Seeking Solutions: Maximizing American Talent by Advancing Women of Color in Academia is the summary of a 2013 conference convened by the Committee on Women in Science, Engineering and Medicine of the National Research Council to discuss the current status of women of color in academia and explore the challenges and successful initiatives for creating the institutional changes required to increase representation of women of color at all levels of the academic workforce. While the number of women, including minority women, pursuing higher education in science, engineering and medicine has grown, the number of minority women faculty in all institutions of higher education has remained small and has grown less rapidly than the numbers of nonminority women or minority men. Seeking Solutions reviews the existing research on education and academic career patterns for minority women in science, engineering, and medicine to enhance understanding of the barriers and challenges to the full participation of all minority women in STEM disciplines and academic careers. Additionally, this report identifies reliable and credible data source and data gaps, as well as key aspects of exemplary policies and programs that are effective in enhancing minority women's participation in faculty ranks. Success in academia is predicated on many factors and is not solely a function of talent. Seeking Solutions elucidates those other factors and highlights ways that institutions and the individuals working there can take action to create institutional cultures hospitable to people of any gender, race, and ethnicity.

Review of Army Research Laboratory Programs for Historically Black Colleges and Universities and Minority Institutions - National Research Council (The National Academies Press, 2014)
Review of Army Research Laboratory Programs for Historically Black Colleges and Universities and Minority Institutions examines the ways in which historically black colleges and universities and minority institutions have used the Army Research Laboratory (ARL) funds to enhance the science, technology, engineering, and mathematics (STEM) programs at their institutions over the past decade. This report also considers which program elements reflect practices that are effective for assisting these institutions in enhancing the STEM programs and could be considered by other Department of Defense agencies for application to their programs. The Army Research Laboratory has contributed to building up the human and infrastructural capacities in the past, and this report looks for ways to enhance ARL program impact on institution-building in the future, confident that more capable black and minority-serving institutions will, in turn, help America as a whole develop a more diverse and intellectually capable STEM workforce.

Barriers and Opportunities for 2-Year and 4-Year STEM Degrees: Systemic Change to Support Students' Diverse Pathways - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine
Nearly 40 percent of the students entering 2- and 4-year postsecondary institutions indicated their intention to major in science, technology, engineering, and mathematics (STEM) in 2012. But the barriers to students realizing their ambitions are reflected in the fact that about half of those with the intention to earn a STEM bachelor's degree and more than two-thirds intending to earn a STEM associate's degree fail to earn these degrees 4 to 6 years after their initial enrollment. Many of those who do obtain a degree take longer than the advertised length of the programs, thus raising the cost of their education. Are the STEM educational pathways any less efficient than for other fields of study? How might the losses be \

Expanding Underrepresented Minority Participation: America's Science and Technology Talent at the Crossroads - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2011)
In order for the United States to maintain the global leadership and competitiveness in science and technology that are critical to achieving national goals, we must invest in research, encourage innovation, and grow a strong and talented science and technology workforce. Expanding Underrepresented Minority Participation explores the role of diversity in the science, technology, engineering and mathematics (STEM) workforce and its value in keeping America innovative and competitive. According to the book, the U.S. labor market is projected to grow faster in science and engineering than in any other sector in the coming years, making minority participation in STEM education at all levels a national priority. Expanding Underrepresented Minority Participation analyzes the rate of change and the challenges the nation currently faces in developing a strong and diverse workforce. Although minorities are the fastest growing segment of the population, they are underrepresented in the fields of science and engineering. Historically, there has been a strong connection between increasing educational attainment in the United States and the growth in and global leadership of the economy. Expanding Underrepresented Minority Participation suggests that the federal government, industry, and post-secondary institutions work collaboratively with K-12 schools and school systems to increase minority access to and demand for post-secondary STEM education and technical training. The book also identifies best practices and offers a comprehensive road map for increasing involvement of underrepresented minorities and improving the quality of their education. It offers recommendations that focus on academic and social support, institutional roles, teacher preparation, affordability and program development.

The Science of Effective Mentorship in STEMM - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Mentorship is a catalyst capable of unleashing one's potential for discovery, curiosity, and participation in STEMM and subsequently improving the training environment in which that STEMM potential is fostered. Mentoring relationships provide developmental spaces in which students' STEMM skills are honed and pathways into STEMM fields can be discovered. Because mentorship can be so influential in shaping the future STEMM workforce, its occurrence should not be left to chance or idiosyncratic implementation. There is a gap between what we know about effective mentoring and how it is practiced in higher education. The Science of Effective Mentorship in STEMM studies mentoring programs and practices at the undergraduate and graduate levels. It explores the importance of mentorship, the science of mentoring relationships, mentorship of underrepresented students in STEMM, mentorship structures and behaviors, and institutional cultures that support mentorship. This report and its complementary interactive guide present insights on effective programs and practices that can be adopted and adapted by institutions, departments, and individual faculty members.

Advancing Diversity, Equity, Inclusion, and Accessibility in the Leadership of Competed Space Missions - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Fostering diverse and inclusive teams that are highly skilled, innovative, and productive is critical for maintaining U.S. leadership in space exploration. In recent years, NASA has taken steps to advance diversity, equity, inclusion, and accessibility (DEIA) in their workforce by releasing its equity action plan, emphasizing how diverse and inclusive teams help maximize scientific returns, and requiring DEIA plans as part of announcements of opportunities. To further its efforts to advance DEIA, the Agency requested the National Academies undertake a study to evaluate ways NASA can address the lack of diversity in space mission leadership. Advancing Diversity, Equity, Inclusion, and Accessibility in the Leadership of Competed Space Missions outlines near and long-term actions NASA can take to make opportunities for leadership and involvement in competed space missions more accessible, inclusive, and equitable. Report recommendations range from changes to the mission proposal process to investments in STEM education and career pathways. This report makes 15 recommendations for advancing DEIA within NASA's Science Mission Directorate divisions that support competed space mission programs. However, many of the report's recommendations could also be applied broadly to research at NASA and other federal agencies and institutions, leading to a more diverse research workforce.

Evaluating the Effectiveness of Interventions to Prevent and Address Sexual Harassment: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Rising awareness of and increased attention to sexual harassment has resulted in momentum to implement sexual harassment prevention efforts in higher education institutions. Work on preventing sexual harassment is an area that has recently garnered a lot of attention, especially around education and programs that go beyond the standard anti-sexual harassment trainings often used to comply with legal requirements. On April 20-21, 2021, the National Academies of Sciences, Engineering, and Medicine hosted the workshop Developing Evaluation Metrics for Sexual Harassment Prevention Efforts. The workshop explored approaches and strategies for evaluating and measuring the effectiveness of sexual harassment interventions being implemented at higher education institutions and research and training sites, in order to assist institutions in transforming promising ideas into evidence-based best practices. Workshop participants also addressed methods, metrics, and measures that could be used to evaluate sexual harassment prevention efforts that lead to change in the organizational climate and culture and\/or a change in behavior among community members. This publication summarizes the presentations and discussion of the workshop.

The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The spring of 2020 marked a change in how almost everyone conducted their personal and professional lives, both within science, technology, engineering, mathematics, and medicine (STEMM) and beyond. The COVID-19 pandemic disrupted global scientific conferences and individual laboratories and required people to find space in their homes from which to work. It blurred the boundaries between work and non-work, infusing ambiguity into everyday activities. While adaptations that allowed people to connect became more common, the evidence available at the end of 2020 suggests that the disruptions caused by the COVID-19 pandemic endangered the engagement, experience, and retention of women in academic STEMM, and may roll back some of the achievement gains made by women in the academy to date. The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine identifies, names, and documents how the COVID-19 pandemic disrupted the careers of women in academic STEMM during the initial 9-month period since March 2020 and considers how these disruptions - both positive and negative - might shape future progress for women. This publication builds on the 2020 report Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine to develop a comprehensive understanding of the nuanced ways these disruptions have manifested. The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine will inform the academic community as it emerges from the pandemic to mitigate any long-term negative consequences for the continued advancement of women in the academic STEMM workforce and build on the adaptations and opportunities that have emerged.

Career Choices of Female Engineers: A Summary of a Workshop - National Research Council; National Academy of Engineering (The National Academies Press, 2014)
Despite decades of government, university, and employer efforts to close the gender gap in engineering, women make up only 11 percent of practicing engineers in the United States. What factors influence women graduates' decisions to enter the engineering workforce and either to stay in or leave the field as their careers progress? Researchers are both tapping existing data and fielding new surveys to help answer these questions. On April 24, 2013, the National Research Council Committee on Women in Science, Engineering, and Medicine held a workshop to explore emerging research and to discuss career pathways and outcomes for women who have received bachelor's degrees in engineering. Participants included academic researchers and representatives from the Department of Labor, National Science Foundation, and Census Bureau, as well as several engineering professional societies. Career Choices of Female Engineers summarizes the presentations and discussions of the workshop.

Minority Serving Institutions: America's Underutilized Resource for Strengthening the STEM Workforce - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
There are over 20 million young people of color in the United States whose representation in STEM education pathways and in the STEM workforce is still far below their numbers in the general population. Their participation could help re-establish the United States' preeminence in STEM innovation and productivity, while also increasing the number of well-educated STEM workers. There are nearly 700 minority-serving institutions (MSIs) that provide pathways to STEM educational success and workforce readiness for millions of students of color2014and do so in a mission-driven and intentional manner. They vary substantially in their origins, missions, student demographics, and levels of institutional selectivity. But in general, their service to the nation provides a gateway to higher education and the workforce, particularly for underrepresented students of color and those from low-income and first-generation to college backgrounds. The challenge for the nation is how to capitalize on the unique strengths and attributes of these institutions and to equip them with the resources, exceptional faculty talent, and vital infrastructure needed to educate and train an increasingly critical portion of current and future generations of scientists, engineers, and health professionals. Minority Serving Institutions examines the nation's MSIs and identifies promising programs and effective strategies that have the highest potential return on investment for the nation by increasing the quantity and quality MSI STEM graduates. This study also provides critical information and perspective about the importance of MSIs to other stakeholders in the nation's system of higher education and the organizations that support them.

Advancing Diversity in the US Industrial Science and Engineering Workforce: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2014)
Thousands of gifted individuals, including women and underrepresented minorities, remain a disproportionally small fraction of those in science, technology, engineering, and math (STEM) careers. Industry, as the largest employer category of those with STEM backgrounds, stands to benefit considerably from greater inclusion of women and underrepresented minorities in the workforce. However, nothing short of a game-changing environment must be created to harness the talent of those not fully represented in the STEM workforce. Advancing Diversity in the US Industrial Science and Engineering Workforce is the summary of a workshop held in May, 2012 by the National Academy of Engineering, focusing on the needs and challenges facing industry in particular, and it is intended to facilitate further discussion and actions to address these complex issues. The workshop provided a forum for leaders from industry, academia, and professional associations to share best practices and innovative approaches to recruiting, retaining, and advancing women and underrepresented minorities in the scientific and engineering workforce throughout the nation's industries.

Sexual Harassment of Women: Climate, Culture, and Consequences in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Over the last few decades, research, activity, and funding has been devoted to improving the recruitment, retention, and advancement of women in the fields of science, engineering, and medicine. In recent years the diversity of those participating in these fields, particularly the participation of women, has improved and there are significantly more women entering careers and studying science, engineering, and medicine than ever before. However, as women increasingly enter these fields they face biases and barriers and it is not surprising that sexual harassment is one of these barriers. Over thirty years the incidence of sexual harassment in different industries has held steady, yet now more women are in the workforce and in academia, and in the fields of science, engineering, and medicine (as students and faculty) and so more women are experiencing sexual harassment as they work and learn. Over the last several years, revelations of the sexual harassment experienced by women in the workplace and in academic settings have raised urgent questions about the specific impact of this discriminatory behavior on women and the extent to which it is limiting their careers. Sexual Harassment of Women explores the influence of sexual harassment in academia on the career advancement of women in the scientific, technical, and medical workforce. This report reviews the research on the extent to which women in the fields of science, engineering, and medicine are victimized by sexual harassment and examines the existing information on the extent to which sexual harassment in academia negatively impacts the recruitment, retention, and advancement of women pursuing scientific, engineering, technical, and medical careers. It also identifies and analyzes the policies, strategies and practices that have been the most successful in preventing and addressing sexual harassment in these settings.

Psychological Factors That Contribute to the Dearth of Black Students in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Efforts over the last several decades to increase the participation and leadership of Black men and women in the scientific and medical workforce have had limited results. Despite many individual successes, the number of Black professionals in science, engineering, and medicine (SEM) fields has not reached a level that corresponds with African American representation in the country at large. Structural racism affects progress at all stages along the pathway - from young children through graduate and medical students through faculty and clinicians at all levels. Beyond entry into educational programs or recruitment into workplaces seeking to diversify, challenges persist to achieve equity and inclusion for Black males and females. Moreover, psychological barriers confound the engagement of Black men and women in SEM fields. To explore these issues and suggest solutions, the National Academies of Sciences, Engineering, and Medicine launched the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine. Over the past 2 years, the Roundtable has convened workshops on K-12 education, the impact of COVID-19, financial burdens to pursuing SEM careers, and other topics. Sessions during each of these workshops identified psychological factors related to those specific topics. To have a more targeted discussion, the Roundtable convened a virtual workshop on September 14-15, 2021. As summarized in this proceedings, panelists and participants identified policies and practices that perpetuate these factors and explored solutions toward achieving and maintaining wellness, especially among students and young professionals.

Transforming Trajectories for Women of Color in Tech - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Demand for tech professionals is expected to increase substantially over the next decade, and increasing the number of women of color in tech will be critical to building and maintaining a competitive workforce. Despite years of efforts to increase the diversity of the tech workforce, women of color have remained underrepresented, and the numbers of some groups of women of color have even declined. Even in cases where some groups of women of color may have higher levels of representation, data show that they still face significant systemic challenges in advancing to positions of leadership. Research evidence suggests that structural and social barriers in tech education, the tech workforce, and in venture capital investment disproportionately and negatively affect women of color. Transforming Trajectories for Women of Color in Tech uses current research as well as information obtained through four public information-gathering workshops to provide recommendations to a broad set of stakeholders within the tech ecosystem for increasing recruitment, retention, and advancement of women of color. This report identifies gaps in existing research that obscure the nature of challenges faced by women of color in tech, addresses systemic issues that negatively affect outcomes for women of color in tech, and provides guidance for transforming existing systems and implementing evidence-based policies and practices to increase the success of women of color in tech.

Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Careers in science, engineering, and medicine offer opportunities to advance knowledge, contribute to the well-being of communities, and support the security, prosperity, and health of the United States. But many women do not pursue or persist in these careers, or advance to leadership positions - not because they lack the talent or aspirations, but because they face barriers, including: implicit and explicit bias; sexual harassment; unequal access to funding and resources; pay inequity; higher teaching and advising loads; and fewer speaking invitations, among others. There are consequences from this underrepresentation of women for the nation as well: a labor shortage in many science, engineering, and medical professions that cannot be filled unless institutions and organizations recruit from a broad and diverse talent pool; lost opportunities for innovation and economic gain; and lost talent as a result of discrimination, unconscious bias, and sexual harassment. Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine reviews and synthesizes existing research on policies, practices, programs, and other interventions for improving the recruitment, retention, and sustained advancement into leadership roles of women in these disciplines. This report makes actionable recommendations to leverage change and drive swift, coordinated improvements to the systems of education, research, and employment in order to improve both the representation and leadership of women.